2018
DOI: 10.12681/ppej.16135
|View full text |Cite
|
Sign up to set email alerts
|

Does theatrical play promote social skills development in students with autism? A systematic review of the methods and measures employed in the literature

Abstract: This systematic review cites a number of programs and critically analyzes methods and measures used to develop social skills in young students with Autism Spectrum Disorders (ASD). Social skills are interpreted through a ToM theory lens, emphasizing interactions such as understanding, explaining, predicting, and manipulating the behavior of themselves and the others. The aim of this review is to study the role of the theatrical play programs and its effect on social interactions and social skills on students w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 22 publications
1
10
0
Order By: Relevance
“…Data has indicated the fact that these relations are not only maintained, but they evolve over time, with a beneficial evolution being seen by comparing data 3 months after the intervention and one year after the intervention. Our data is similar to other data sets found in the specialty literature (Goldingay et al, 2013;Mpella & Evaggelinou, 2018).…”
supporting
confidence: 89%
See 1 more Smart Citation
“…Data has indicated the fact that these relations are not only maintained, but they evolve over time, with a beneficial evolution being seen by comparing data 3 months after the intervention and one year after the intervention. Our data is similar to other data sets found in the specialty literature (Goldingay et al, 2013;Mpella & Evaggelinou, 2018).…”
supporting
confidence: 89%
“…This calls for the use of communicational and relational abilities, problem solving abilities, teamwork (in pairs or in small groups), a high degree of flexibility and receptivity towards other's ideas and suggestions (O'Sullivan, 2015). Mpella and Evaggelinou (2018) have identified in their meta-analysis that theatrical games have a positive impact on the enhancement of communicational abilities, social interaction, cooperation and social awareness. Wheater (2013) has found that using theatrical activities has a positive impact not only in the case of children with ASD, but also in the case of neurotypical children, the benefits being observed on both sides (Mpella & Evaggelinou, 2018), which is why we believed that this technique can be an efficient one in aiding the school inclusion of children with ASD.…”
Section: Problem Statementmentioning
confidence: 99%
“…Complementary backward chaining was also conducted given that database searching is not exhaustive (Evans & Benefield, 2001). The reference lists of the seminal articles identified (and listed) above were searched for eligible studies alongside the examination of the bibliographies of previous systematic reviews in the area (Alagendran et al, 2019;Cornell et al, 2018;Gibson et al, 2020;Godin et al, 2019;Jung & Sainato, 2013;Kent et al, 2020a;Kossyvaki & Papoudi, 2016;Kuhaneck et al, 2020;Lai et al, 2018;Lang et al, 2011;Lindsay et al, 2017;Lory et al, 2018;Mpella & Evaggelinou, 2018;Pyle et al, 2017). Overall, this process yielded an additional 130 citations resulting in a total of 1041 articles for potential inclusion.…”
Section: Systematic Search Proceduresmentioning
confidence: 99%
“…Students, through their identification with a role, try to become the other, to feel like the other, to experience how the other sees things. It is a process that releases consciousness, transforms it and leads to empathy and intercultural communication (Adorno, 1970;Kosti et al, 2015;Mpella & Evaggelinou, 2018;Papaioannou & Kontoyanni, 2019;Mavroudis, 2020).…”
Section: Drama In Education and Physical Educationmentioning
confidence: 99%